Penetration of moxalactam into its target proteins in Escherichia coli K-12: comparison of a highly moxalactam resistant mutant with its parent strain. - Komatsu, Y (1981)
An eschericia coli K-12 mutant highly resistant to moxalactam but only slightly resistant to other beta-lactam antibiotics was obtained by mutagen treatment. The affinity of moxalactam for its target penicillin-binding proteins was unchanged, as was the level of beta-lactamase activity. The penetration of [14C] moxalactam, however, was markedly reduced in the mutant. Electrophoretic analysis revealed alterations of the outer membrane proteins. A reduction in the amount of one of the pore-forming proteins (porins) was especially noteworthy. These data suggest that moxalactam resistance is the result of an alteration in the outer membrane structure.